Towards defining core principles of public health emergency preparedness: scoping review and Delphi consultation among European Union country experts - Evelien Belfroid; Dorothee Roβkamp; Graham Fraser; Corien Swaan; Aura Timen (BMC, 2020)
Abstract Background European Member States, the European Commission and its agencies work together to enhance preparedness and response for serious cross-border threats to health such as Ebola. Yet, common understanding of public health emergency preparedness across EU/EEA countries is challenging, because preparedness is a relatively new field of activity and is inherently fraught with uncertainty. A set of practical, widely accepted and easy to use recommendations for generic preparedness that bundles the activities described in separate guidance documents supports countries in preparing for any possible health threat. The aim of this consensus procedure was to identify and seek consensus from national-level preparedness experts from EU/EEA countries on key recommendations of public health emergency preparedness. Methods To identify key recommendations and to prioritize the recommendations we started with a literature consensus procedure, followed by a modified Delphi method for consultation of public health emergency preparedness leaders of EU/EEA countries. This consisted of six consecutive steps: a questionnaire to achieve consensus on a core set of recommendations, a face-to-face consultation, preselection of prioritized recommendations, a questionnaire to achieve consensus on the prioritized set and a face-to-face consensus meeting to further prioritize recommendations. Results As a result, EU/EEA experts selected 149 recommendations as core preparedness principles and prioritized 42. The recommendations were grouped in the seven domains: governance (57), capacity building and maintenance (11), surveillance (19), risk-assessment (16), risk- and crisis management (35), post-event evaluation (6) and implementation of lessons learned (5). Conclusions This prioritised set of consensus principles can provide a foundation for countries aiming to evaluate and improve their preparedness for public health emergencies. The recommendations are practical, support generic preparedness planning, and can be used by all countries irrespective of their current level of preparedness.